Make it anew - Ibelings, Hans 1963- (The Architecture Observer, 2018)
Architecture builds upon history. Even the avant-gardist creed to 'make it new' still assumes a past. It is impossible to imagine novelty without an awareness of what existed before. This is even more true for the reuse and appropriation of existing structures, where designers take a stance relative to the past. In their transformation projects the office of diederendirrix architects retell stories of buildings and sites - by paraphrasing part of the story, by recasting central actors, by making architecture speak in other words. In so doing, they make it anew. Written, compiled, and edited by architecture critic Hans Ibelings in collaboration with Paul Diederen and Bert Dirrix
Keywords: Ibelings, Hans -- 1963-; Diederendirrix -- Firma; Diederendirrix architects / Catalogs; Architecture / History / Designs and plans; Architecture; Architectural drawings; Catalogs; History; Bildband